Construction of Smart Manganese Dioxide‐Based All‐in‐One Nanoplatform for Cancer Diagnosis and Therapy. Issue 12 (13th September 2020) - Liu, Xiangmei; Zhou, Yanli; Xie, Wangwang; Liu, Shujuan; Zhao, Qiang; Huang, Wei
Abstract: Manganese dioxide (MnO2 )‐based functional nanomaterials have attracted great attention in the fields of nanoscience, biosensors, bioimaging, drug/gene delivery, and cancer therapy. Especially, all‐in‐one tumor microenvironment (TME) responsive MnO2 ‐based nanoagents have become a research hotspot due to their simple fabrication procedure, high specific surface area, controllable size and morphologies, easy surface modification, TME response, and oxygen generation. This review aims to provide a comprehensive overview of strategies for construction of MnO2 ‐based all‐in‐one nanoplatforms for cancer diagnosis and therapy. Major highlighted topics in this paper focus on the controllable fabrication of MnO2 nanobuilding blocks, tumor targeting accumulation, working mechanisms of enhancing therapeutic efficacy, and the necessary considerations for construction of all‐in‐one nanoplatform. Finally, the current challenges and future directions in this rapidly growing research field are also discussed, which will provide guidance on the future works about the clinical translation of MnO2 ‐based all‐in‐one nanoplatform. Abstract : Strategies to design all‐in‐one MnO2 ‐based nanoplatforms for precise and synergistic therapy are systematically summarized, from the controllable fabrication of MnO2 nanobuilding blocks, targeting tumor accumulation, working mechanisms for enhancing therapeutic efficacy to the necessary considerations for construction of all‐in‐one nanoplatform.